CAREC corridor performance measurement and monitoring annual report 2018. (Metro Manila, Philippines Asian Development Bank, 2019)
The data show steady average improvement in speed without delay, largely attributed to infrastructure investment. Delays at the border decreased but remain a major hindrance to efficient trade. This report informs policymakers about transport and trade blockages, and aims to help guide infrastructure investment and trade facilitation reform and modernization.
Keywords: Infrastructure (Economics) -- Central Asia; Infrastructure (Economics) -- Developing countries -- Finance; Electronic books